Association of anthropometric indicators and blood pressure with subclinical cardiovascular diseases in obese adolescents: a cross-sectional study - Liu, Xiaohui; Xu, Shuang; Wang, Jing; Feng, Yan; Xia, Yuwen; Yuan, Xiaofeng; Tang, Ruijing; Lu, Kai; Shao, Jun (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCarotid–femoral pulse wave velocity, carotid intima–media thickness (cIMT) and left ventricular hypertrophy are early measures of future subclinical cardiovascular disease (CVD) events. Although the associations between body mass index (BMI), abdominal adiposity measures, blood pressure, and CVD have been relatively well studied in adults, the evidence in children and adolescents is limited. Therefore, this study aimed to investigate the associations between BMI, abdominal obesity indices, blood pressure levels, and cIMT among obese adolescents in Jiangsu Province, China, and to identify potential critical thresholds.MethodsA stratified cluster sampling method was used to select participants from primary, middle, and high schools in Jiangsu Province. Clinical examinations included anthropometric measurements, blood sampling, and ultrasound assessments. cIMT was measured via carotid ultrasound. Statistical analyses, including Spearman correlation coefficients, nonlinear fitting, piecewise regression and multiple linear regression, were conducted to explore the associations between BMI, abdominal obesity indicators, blood pressure levels, and cIMT in obese adolescents.ResultsAmong the 245 obese adolescents, the waist‒to-hip ratio (WHR), BMI, systolic blood pressure (SBP), and diastolic blood pressure (DBP) were significantly positively correlated with cIMT (P < 0.001).Nonlinear fitting and piecewise regression revealed that right cIMT increased sharply with SBP > 115.7 mmHg, DBP > 70.9 mmHg, BMI > 26.0 kg/m2; left cIMT increased sharply with SBP > 131.0 mmHg, DBP > 81.8 mmHg, BMI > 33.0 kg/m2, and WHR > 0.84. Multivariate analysis indicated that only SBP maintained an independent association with left cIMT (P < 0.05).ConclusionOur study revealed a significant association between anthropometric measures and cIMT in obese adolescents, and these factors can be used as early markers of subclinical CVD. Early intervention for BP control may help reduce long-term CVD risk in this population.